The pathophysiological role of heat shock response in autoimmunity: A literature review - Androvitsanea, Ariadni; Stylianou, Kostas; Drosataki, Eleni; Petrakis, Ioannis (Cells, 2021)
Within the last two decades, there has been increasing evidence that heat-shock proteins can have a differential influence on the immune system. They can either provoke or ameliorate immune responses. This review focuses on outlining the stimulatory as well as the inhibitory effects of heat-shock proteins 27, 40, 70, 65, 60, and 90 in experimental and clinical autoimmune settings.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Autoimmunity; Heat-shock proteins; Heat-shock response